2010
DOI: 10.1177/0886109910364824
|View full text |Cite
|
Sign up to set email alerts
|

Graduating Social Work Students’ Perspectives on Domestic Violence

Abstract: This article reports the findings of a qualitative study that examined 124 social work students' views on the causes and dynamics of domestic violence and their recommended interventions in a case scenario. Most students graduated from the master of social work (MSW) program with a mental health perspective on domestic violence. Only a small percentage were aware of specific interventions for domestic violence and many continued to attribute domestic violence to mental health and substance abuse problems in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 27 publications
(30 reference statements)
1
43
0
7
Order By: Relevance
“…Correspondingly, education is an important role of social workers and an intervention that they are often comfortable in recommending and performing (Asquith, Clark, & Waterhouse, 2005;Black et al, 2010;Hepworth, Rooney, Rooney & Strom-Gottfried, 2013). It is a strength that graduating social workers would instruct clients on healthy relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, education is an important role of social workers and an intervention that they are often comfortable in recommending and performing (Asquith, Clark, & Waterhouse, 2005;Black et al, 2010;Hepworth, Rooney, Rooney & Strom-Gottfried, 2013). It is a strength that graduating social workers would instruct clients on healthy relationships.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies have found that previous training and coursework have little impact on attitudes and beliefs about violence against women (Postmus et al, 2011;Tower, 2003) and raise concerns about students' readiness to intervene effectively with clients experiencing IPV. Black, Weisz, and Bennett's (2010) examination of social work students' probable interventions in response to a case scenario found that even though almost 20% of the students had taken an elective class on family violence, few mentioned IPV-specific interventions and one-third included statements that blamed the victim for the occurrence of violence. This study also found that a majority of students believed IPV to be a mental health issue and recommended counseling, an idea consistent with Danis and Lockhart's (2003) assertion that social work students view IPV as a mental health problem of the victim.…”
Section: Social Work Education and Intimate Partner Violencementioning
confidence: 99%
“…Despite distinct evidence of domestic violence as a social problem, intimate partner violence carries its own set of inherent interpersonal judgments. Some common beliefs include the notion that women's behavior contributes to their experience of violence, some women want to be abused, and women can easily leave abusive relationships (Black, Weisz & Bennett, 2010;Worden & Carlson, 2005). Crenshaw (1991) defined intersectionality as a useful framework with which to mediate the tensions between assertions of multiple identities and the ongoing necessity of group politics.…”
Section: Faulty Domestic Violence Assumptionsmentioning
confidence: 99%
“…Professionally, the role of critical thinking in a context of clinical awareness cannot be underrated. Clinicians implement critical thinking in relation to risk in both assessment and practice (Black, Weisz & Bennett, 2010), which is typically research or evidence informed. However, Taleff (2006) noted that practitioners frequently assess clients with limited information and fill in gaps with their own ideas, emotions and assumptions; this was consistent with my personal experience.…”
Section: Practitioner Education and Trainingmentioning
confidence: 99%
“…Research supports the argument that male's abuse of their intimate partners is used in dominant traditional patriarchal power structures to enforce women's inequality and submissiveness (Black, Weisz, & Bennett, 2010;Goonesekere, 2006;Mullaly, 2002), and further, that physical violence is one way of men's obtaining, and maintaining power and control over their female partner (Leone, Lape, & Xu, 2014). Participants' experiences reveal emotional, verbal, mental, and economic abuse.…”
Section: Contrasting Results To the Literature Similaritiesmentioning
confidence: 84%